Shaft friction changes for cyclically loaded displacement piles: an X-ray investigation. Issue 1 (27th February 2018) - Doreau-Malioche, J.; Combe, G.; Viggiani, G.; Toni, J. B.
Abstract : The mechanisms occurring at the grain scale at sand–pile interface under axial cyclic loading are analysed quantitatively in a mini calibration chamber, using X-ray tomography and three-dimensional-digital image correlation. Grain kinematics and porosity evolution are followed along with the macroscopic mechanical response of the interface. The results show different phases in the evolution of shaft resistance during cyclic loading, with a non-negligible increase of shaft resistance in the latter phase. The test conditions are not representative of real engineering applications, where piles supporting bridges, tidal or wind turbines have to safely sustain severe load-controlled cycles. However, advanced image analysis sheds light on the mechanisms controlling the macroscopic behaviour of sand–pile interface. This study provides valuable data set against which theoretical or numerical approaches can be tested.